Software educacional para dimensionamento de ligações em madeira por pinos metálicos - Mello, Gabriela Karina Morais de (2017)
The connections are known as critical structural regions due to their function of transmiting internal forces between the connected elements. Because of their importance in the global behavior of the structure, the connection's design and execution must be done precisely to assure the structure's safety. When manually done, the design calculations are quite extensive and complex, but with the computing advance, it is possible to develop softwares capable of making that task easier. Currently, the Brazilian code for timber structures design ABNT NBR 7190 (1997) is being revisited, and one of its recently altered subjects was the design of connections with metal pins. In order to help the academics and the professionals of construction in learning this new design procedure, a software was created for design the connections with metal pins, which includes connections with nails and bolts. The software is called TCD (Timber Connections Design) – Version 2.0.